Огляд стану розвитку систем мобільного зв'язку - Бабак, К. В. (My University, 2021)
There are many new technologies and technologies that will be used in the new 5G cellular or mobile telecommunications system. However, these new 5G technologies are still being developed and common standards have not yet been defined. However, as the necessary technologies develop, they will be included in a new system to be defined by standardization bodies in the coming years.
Keywords: 5G technologies; mobile telecommunications system; 5G